Antioxidant Capacity, Lipid Oxidation, and Quality Traits of Slow- and Fast-Growing Meagre (Argyrosomus regius) Fillets During Cold Storage - Ioannis Mittakos; Cosmas I. Nathanailides; Lambros E. Kokokiris; Alexandra Barbouti; Konstantina Bitchava; Evangelia Gouva; Markos N. Kolygas; Michael A. Terzidis; Michael G. Kontominas (Antioxidants)
Meagre (Argyrosomus regius) is an important species in aquaculture, with size and flesh quality playing key roles in its production and marketability. This study aimed to examine the relationship between growth and flesh quality parameters, including fatty acid content (FA), total antioxidant capacity (TOAC), superoxide dismutase (SOD), lipid oxidation (LO), muscle cellularity (MC), and filleting yield (FY) during cold storage. Fish from the same hatchery raised under identical conditions showed size variation after 12 months. Fish below 600 g were classified as slow growing (SG), while those above 1000 g were classified as fast-growing (FG). The results showed that FG fish had higher body weight, moisture, and FY but exhibited lower levels of fat and polyunsaturated fatty acids (PUFA). SG fish had higher TOAC and SOD activity, which significantly declined during cold storage in both groups but remained higher in SG fish. Despite the higher lipid content in SG fish, no significant differences in malondialdehyde (MDA) levels, an indicator of LO, were observed between the two groups, suggesting that the elevated antioxidant defenses in SG fish mitigated lipid peroxidation. This study underscores intrinsic antioxidants’ potential to preserve lipid quality of fish fillets during cold storage.